The specialist physician’s approach to rheumatoid arthritis in South Africa - Bester, Frederik C. J. (Korean J Intern Med, 2016)
Rheumatoid arthritis (RA) is expected to increase in Africa and South Africa. Due to the low numbers of rheumatologists in South Africa, specialist physicians also have to care for patients with RA. Furthermore several new developments have taken place in recent years which improved the management and outcome of RA. Classification criteria were updated, assessment follow-up tools were refined and above all, several new biological disease-modifying anti-rheumatic drugs were developed. Therefore it is imperative for specialist physicians to update themselves with the newest developments in the management of RA. This article provides an overview of the newest developments in the management of RA in the South African context. This approach may well apply to countries with similar specialist to patient ratios and disease profiles.